Reading Humor in David Cronenberg's Crash - Petsota, Myrto (Transcr(é)ation, 2024)
David Cronenberg’s statement that “The film is funny, the book is not very funny” (1997) presents a captivating paradox regarding his adaptation of J. G. Ballard’s Crash. This statement reveals Cronenberg as both an insightful and superficial reader of Ballard. His film adaptation chooses to remain faithful to many aspects of the source material and retains the subtle undercurrents of humor found in the book, often overlooked and unrecognized by both the director and audiences, as well critics. Paradoxically, the film’s reception has further obscured this aspect of his work. The paper delineates the mechanics of humor in Crash, applying Freudian and Bergsonian theories linking humor to anxiety relief and behavioral correction. It spotlights Ballard’s absurd character speculations and detached narrative voice juxtaposing poetic violence, while Cronenberg conveys humor via affectless performances, anti-climactic sex, and self-referential jokes exposing cinematic artifice. Further analysis explores Ballard’s satire through the parody of melodramatic tableaux versus Cronenberg’s meta-cinematic parody of Hollywood and the road movie genre, noting that the adaptation compresses the novel’s sociopolitical critique but expands its intertextuality. The article challenges assumptions that humor must be light or affirming, arguing that the unsettling, avant-garde laughter in Crash (1973, 1996) compels reflection on technology’s impacts on identity. Ultimately, recognizing the dark comedy in Crash and its adaptation illuminates their lingering cultural commentary on dehumanization rather than celebrating the pathology of the characters.